A non-autonomous stochastic predator-prey model - Aniello Buonocore; Luigia Caputo; Enrica Pirozzi; Amelia G. Nobile (Mathematical Biosciences and Engineering)
The aim of this paper is to consider a non-autonomous predator-prey-like system, with a Gompertz growth law for the prey.By introducing random variations in both prey birth and predator death rates,a stochastic model for the predator-prey-like system in a random environment is proposed and investigated.The corresponding Fokker-Planck equation is solved to obtain the joint probability density for the prey and predator populations and the marginal probability densities.The asymptotic behavior of the predator-prey stochastic model is also analyzed.